(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. CKD is one of the most prevalent entities associated with high morbidity and mortality. Most of the patients with renal diseases, particularly patients undergoing dialysis, suffer from cardiovascular disease and it is necessary to employ appropriate strategies to prevent and manage this complication. The aim of this study was to evaluate the anti-inflammatory effects of omega-3 in patients undergoing CAPD. Methods. Nineteen CAPD patients with certain inclusion and exclusion criteria enrolled in this study. Omega-3 capsules with a dose of 1 g/d up to three months, were administrated. Some inflammatory markers such as ESR, CRP, HS-CRP, IL-6, MDA, and homocysteine were measured in three phases. In addition, lipid profile including triglyceride, cholesterol, LDL, and HDL were measured. Results. Results of this study showed that CRP, HS-CRP, and homocysteine levels increased insignificantly (P > .05) whereas, MDA level was increased significantly (P < .05). ESR and IL-6 levels both decreased but did not show any statistically significance (P > .05). Results of lipid profile also suggested that none of the lipid levels changed significantly (P > .05). Conclusion. It is necessary to design large trials in order to understand clear effects of omega-3 on inflammatory markers in PD patients. In addition, the results of this current pilot study should be interpreted with caution.